MemorIA, an Architecture for Creating Interactive AI Historical Agents in Educational Contexts - Oger, Antoine; Gorisse, Geoffrey; Fleury, Sylvain; Christmann, Olivier (Computer animation and virtual worlds, 2025)
ABSTRACT This article presents the architecture of MemorIA, an integrative system that combines existing AI technologies into a coherent educational framework for creating interactive historical agents, with the aim of fostering students' learning interest. MemorIA generates animated digital portraits of historical figures, synchronizing facial expressions with synthesized speech to enable natural conversations with students. The system leverages NVIDIA Audio2Face for real‐time facial animation with first‐order motion model for portrait manipulation, achieving fluid interaction through low‐latency audio‐visual streaming. To assess our architecture in a field situation, we conducted a pilot study in middle school history classes, where students and teachers engaged in direct conversation with a virtual Julius Caesar during Roman history lessons. Students asked questions about ancient Rome, receiving contextually appropriate responses. While qualitative feedback suggests a positive trend toward increased student participation, some weaknesses and ethical considerations emerged. Based on this assessment, we discuss implementation challenges, suggest architectural improvements, and explore potential applications across various disciplines. MemorIA enables students to interact with AI‐powered historical characters like Julius Caesar through real‐time animated portraits and synthesized speech.